Assessment of Depression among IBD patients in Gastroenterology and Hepatology Specialized Hospital, Medical City, Iraq using the PHQ-9 - Hani alraeai; Hadeer Kh. Hasan; Zainab A. Abdulameer; Qusay Y. Hamad (مجلة كلية الطب, 2024)
Background: The management of patients with inflammatory bowel disease (IBD) must take mental health into account because it might be difficult to find the best therapies and mental health resources. Anxiety and depression are the two psychological illnesses that IBD patients experience most frequently. The growing incidence of these mental illnesses encourages mental screening of every IBD patient at the initial session. There are easy-to-use, scientifically effective screening techniques for mental health issues. As important as or even more so than a therapy modality may be psychological techniques.